2016
DOI: 10.1016/j.maturitas.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of sleep disturbance in menopausal transition

Abstract: a b s t r a c tObjective: This follow-up study aimed to evaluate risk factors for menopausal sleep disturbances already identifiable before menopause. Methods: At baseline, all 81 women were premenopausal. At year-five follow-up, 27 of the women were premenopausal, 40 postmenopausal, and 14 postmenopausal and using hormone therapy. We used the Basic Nordic Sleep Questionnaire to study sleep; additional questionnaires evaluated risk factors for sleep impairment.Results: Sleep quality differed only marginally be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 35 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…Sleep problems are multifactorial, strongly associated with HFs and depression (as discussed later), as well as other factors coincident with aging into midlife including stress, poor health and chronic pain. 25 , 36 , 37 There is also an age-related increase in the presence of sleep-related breathing and movement disorders, as discussed later. These factors may also interact with each other, providing a complex basis for sleep difficulties in midlife women.…”
Section: Sleep Difficulties Reported Across the Menopausal Transitionmentioning
confidence: 93%
“…Sleep problems are multifactorial, strongly associated with HFs and depression (as discussed later), as well as other factors coincident with aging into midlife including stress, poor health and chronic pain. 25 , 36 , 37 There is also an age-related increase in the presence of sleep-related breathing and movement disorders, as discussed later. These factors may also interact with each other, providing a complex basis for sleep difficulties in midlife women.…”
Section: Sleep Difficulties Reported Across the Menopausal Transitionmentioning
confidence: 93%
“…During the transition to menopause, around 43%‐47% of women will experience some kind of sleep disturbance, while they are also experienced by 15% of the general population but a 5 years follow‐up study found frequent night sweats, depressive symptoms, use of central nervous system medication, personal crises and unsatisfactory perceived health as predictors for poor sleep after menopause . The studies that objectively compared sleep patterns, via PSG or similar methods, during menopausal transition, are few and limited in number of patients and nights evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Among postmenopausal women, this value varies from 40 to 60%, and it is 48% in perimenopause according to the study by Kloss et al 2,3 In the present study, the PSQI was used to assess sleep quality, with sensitivity and specificity of 98.3 and 90.2%, respectively, according to Zhang et al 1 Our results show that 57.28% of menopausal women presented poor sleep or sleep disturbance -values within the means for adults and climacteric, and above that for perimenopause. Considering this prevalence, the importance of this symptom is closely monitored in women during this period of life.…”
Section: /5 Menopausementioning
confidence: 95%
“…1,2 This study focuses on sleep quality in postmenopausal women. Justification is based on the fact that 40 to 60% of women report sleep disturbance during menopause, and the etiology of this impairment is probably multifactorial.…”
Section: Introductionmentioning
confidence: 99%